PENGEMBANGAN ALGORITMA CAESAR CIPHER UNTUK MENGAMANKAN DATA NASABAH APLIKASI TABUNGAN - Solichul Huda; Ferdian Nur Fariza (Fakultas Teknik Universitas Wahid Hasyim, 2025)
Savings customer data needs to be secured to prevent access by unauthorized users, one of which can be done through encryption. Text data encryption can be performed using the Caesar Cipher algorithm. However, the use of this algorithm has several weaknesses, one of which is that it can be broken using the exhaustive key search method. This paper develops a modified Caesar Cipher algorithm to overcome these weaknesses. The proposed method introduces a second key in a multiple substitution process based on the letter order in the plaintext. From the experiments conducted, the exhaustive key search method was unable to decrypt this encryption illegally, and the process remains simple. The proposed Caesar Cipher development can secure text data better than the traditional multiple-key Caesar Cipher algorithm